Laryngeal ultrasound for the prediction of severe laryngomalacia. - Arisa Duantaweesook; Vannipa Vathanophas; Kitirat Ungkanont; Archwin Tanphaichitr; Thanakrit Wannarong; Ramida Amornsitthiwat (PLoS ONE)
Background Laryngeal ultrasound (LUS) is a noninvasive, painless, and radiation-free imaging method that presents a promising alternative, especially for the dynamic assessment of laryngeal structures. It can also be utilized by general practitioners. This study assesses the diagnostic accuracy, patient comfort, and cost-effectiveness of LUS compared to flexible fiberoptic laryngoscopy (FFL) for diagnosing laryngomalacia in infants aged ≤ 2 years with stridor-specific airway issues. Methods A total of 43 infants presented with inspiratory stridor or other airway symptoms and underwent assessments using both flexible fiberoptic laryngoscopy and laryngeal ultrasound. Laryngomalacia was diagnosed based on a vocal fold-arytenoid abduction angle of ≤120° and arytenoid and/or vocal fold collapse during inspiration. The diagnostic performance of LUS was compared with FFL, and the severity of the disease was evaluated. Both the pediatric endoscopist and radiologist were blinded to the patients' diagnoses and study results. Results A total of participants was included in the study, comprising 35% males and 65% females. The mean age of 4.52 ± 5.44 months and the mean weight of 4.62 ± 2.23 kg. Laryngomalacia was diagnosed in 60% of cases using FFL, with seven infants requiring surgical intervention; all were also identified as having laryngomalacia via LUS. LUS demonstrated diagnostic efficiency for laryngomalacia in 7 out of 19 infants, with a sensitivity of 26.92%, specificity of 100%, negative predictive value of 47.22%, and positive predictive value of 100%. The overall diagnostic accuracy of LUS was 55.8%. Conclusion While LUS cannot replace FFL as the primary diagnostic tool for infant laryngomalacia, it serves as a valuable adjunct for follow-up assessments and for identifying moderate to severe cases that may require surgical intervention. Further research and advancements in ultrasound technology may enhance diagnostic accuracy and broaden clinical applications for general practitioners.